Education and trust: A tale of three continents - Guemes, Cecilia; Herreros, Francisco (International Political Science Review)
To date, most research finds education to have a positive effect on trust. Education increases people$1 (Bs social intelligence, making them better able to distinguish between trustworthy and opportunistic types. Alternatively, education allows people to attain privileged social status, making them more resistant to deceit and exploitation by opportunistic types. In this article we show that this is not always the case. The relationship between education and trust is mediated by state efficacy; where the state is relatively efficacious, trustworthy types largely survive, while the opposite is true with relatively weak states. In weak states, highly educated people should be the least trustful. We empirically demonstrate this theoretical insight with survey data from three continents, Europe and Africa at the extremes and Latin America in the middle. We provide some indirect evidence in favor of social intelligence as the key mechanism linking education and trust. - Reproduced.s
Keywords: Trust